Gradient-Echo MR Imaging of the Cervical Spine: Evaluation of Extradural Disease - VanDyke, Carolyn; Ross, Jeffrey S.; Tkach, Jean; Masaryk, Thomas J.; Modic, Michael T. (American Journal of Neuroradiology, 1989)
A prospective study was undertaken on 204 consecutive patients comparing low flip angle gradient-echo and T1-weighted spin-echo techniques in the MR evaluation of cervical extradural disease. Four patient groups were studied with varying gradient-echo TEs (6 or 13 msec) and flip angles (10° or 60°). Images were evaluated independently for contrast behavior and anatomy, then directly compared for conspicuity of lesions. The FLASH sequences (especially with a 10° flip angle) produced better conspicuity of disease in half the imaging time. T1-weighted spin-echo sequences were more sensitive to marrow changes and intradural disease. The short TE sequence (6 msec) did not produce any diagnostic advantage over the longer TE sequence (13 msec). A fast and sensitive MR examination for cervical extradural disease combines a sagittal T1-weighted spin-echo acquisition with sagittal and axial FLASH 10° sequences.